Determinants of FDI location in Egypt: Empirical analysis using governorate panel data - Shima'a Hanafy (Philipps-University Marburg, Faculty of Business Administration and Economics, 2015)
We empirically analyse the determinants of inward foreign direct investment (FDI) in Egypt employing a novel panel dataset of 26 Egyptian governorates for the period 1992 - 2008. Using the case of Arab FDI to Egypt, we also investigate whether FDI location determinants are different depending on similarity of culture and language between FDI source and host region. Our results indicate that domestic private investment, well-functioning Free Zones, and labour abundance positively affect FDI location. In contrast to results for other countries, we find no significant effect of concentration of previous FDI stocks on the location of inward FDI. Moreover, regional investment preferential policies in Egypt - with the exception of Free Zones - do not affect the unequal spatial FDI distribution. Finally, we find that the location of Arab FDI inflows to Egypt is not sensitive to the usual determinants. Arab investors are more willing to invest in less investment-agglomerated areas and are less affected by economic considerations and incentives.
Keywords: F21; E22; R12; O53; Z10; 330; Foreign Direct Investment; FDI location; agglomeration; cultural similarity; regional FDI; Arab countries